Utilization of Generative AI in High School Learning: Opportunities and Challenges Analysis - Saputra, Dhanar Intan Surya; Riyanto; Darmayanti, Irma; Kuncoro, Adam Prayogo (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Study This aims to analyze opportunities and challenges in implementing generative AI technologies, such as ChatGPT and DeepSeek, in learning at the level of intermediate school in Indonesia. The approach is qualitative and descriptive based on studies, cases, and research. This is to study document policy, report education, and literature exploring readiness source power, integration processes and impacts implementation technology. The research results show that generative AI potential increases students’ motivation and participation, primarily through learning media interactive and personalized material. However, there are obstacles in form gap in digital access and lack of it related to teacher training AI technology. In conclusion, the success of the implementation of generative AI relies heavily on equity digital infrastructure, training sustainable for power educators, and proper supervision of policies. Novelty from study This lies in mapping integrative opportunities and obstacles to generative AI implementation in context education middle in Indonesia. Recommendations policy covering improvement of digital access nationally, compilation guidelines on using AI in schools, and periodic evaluation of the effectiveness of AI-based learning.